Catalina Toro-Peréz Julio Fierrro-Morales, Sergio Coronado, Tatiana Roa, eds. Minería, territorio y conflicto en Colombia. Bogotá: Universidad Nacional de Colombia, 2012. 510 pp. - Ramírez Cuellar, Francisco (2015)
null